Philosophy of Science as a Framework for Improving the Quality of Scientific Writing in Islamic Education - Fijrah Hayati Alis; Efendi; Muhammad Zalnur (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
The quality of scientific writing is an important indicator in the development of a scientific discipline, including Islamic Education. This study aims to analyze the role of philosophy of science as a framework in improving the quality of scientific writing in Islamic Education. Using a library research approach, this study examines literature related to the philosophy of science, Islamic epistemology, and the problems of academic writing in Islamic Education. The results of the study indicate that the role of philosophy of science in research and scientific writing in Islamic Education is very fundamental. Ontology plays a role in determining the focus of research and the definition of variables to be analyzed, epistemology serves as a foundation that allows research to proceed systematically and produce valid and measurable scientific work, and axiology serves as a reference for values in writing scientific papers. Axiology also prevents researchers from plagiarism, misinterpretation, and misuse of research results. By consistently applying the three pillars of philosophy of science, scientific works in Islamic education will be more valid, ethical, and make a real contribution to the development of science and educational practice.